The Combined Effect of Smoking and Obesity on Hypertension: Implications for Clinical Management - Aragiannis, Dimitrios; Kasiakogias, Alexandros; Iliakis, Panagiotis; Sagris, Marios; Tatakis, Fotios Panagiotis; Manta, Eleni; Andrikou, Ioannis; Konstantinidis, Dimitrios; Tsioufis, Konstantinos (Current Hypertension Reviews, 2025)
A significant proportion of hypertensive patients are both smokers and obese. Several pathophysiological mechanisms are involved in the combined effect of smoking and obesity on hypertension onset and maintenance. These include increased sympathetic nervous system activity, endothelial dysfunction, inflammation, oxidative stress, and insulin resistance. The presence of these major cardiovascular risk factors may lead to difficult-to-control hypertension as well as substantially increase the risk for an adverse cardiovascular outcome. It is, therefore, imperative that healthcare providers embrace a comprehensive, multifaceted approach in the management of obese hypertensive patients with smoking habits. This review delves into the complex interplay of these risk factors, providing a comprehensive overview of the current literature to aid the deployment of effective clinical management strategies toward reducing the risk profile of affected individuals.
Keywords: smoking